Can You Buy Sperm Donor Identification? An Experiment. Issue 4 (23rd October 2013) - Cohen, I. Glenn; Coan, Travis G.
Abstract : In the United States, most sperm donations are anonymous. By contrast, many developed nations require sperm donors to be identified, typically requiring new sperm (and egg) donors to put identifying information into a registry that is made available to a donor‐conceived child once he or she reaches the age of 18. Recently, advocates have pressed U.S. states to adopt these registries as well, and state legislatures have indicated openness to the idea. This study relies on a self‐selected convenience sample to experimentally examine the economic implications of adopting a mandatory sperm donor identification regime in the United States. Our results support the hypothesis that subjects in the treatment (nonanonymity) condition need to be paid significantly more, on average, to donate their sperm. When restricting our attention to only those subjects who would ever actually consider donating sperm, we find that individuals in the control condition are willing to accept an average of $43 to donate, while individuals in the treatment group are willing to accept an average of $74. These estimates suggest that it would cost roughly $31 per sperm donation, at least in our sample, to require donors to be identified. This price differential roughly corresponds to that of a major U.S. sperm bank that operates both anonymous and identity release programs in terms of what it pays donors.